Pengaruh Air Fuel Ratio Terhadap Emisi Gas Buang Berbahan Bakar Lpg Pada Ruang Bakar Model Helle-Shaw Cell - Tenaya, I Gusti Ngurah Putu; Hardiana, Made (Jurnal Energi Dan Manufaktur, 2012)
The progress of developing science and technology are really influence to human life. Expansion of automotive astransportation and machine mover, can help human to do their activities easily. To get the machines move, is need much offuel from petroleum stock. But the stock of petroleum in world every day is very diminish and its unrenewable. Toanticipation and solve the problem about ability and dependence of society to use the fuel, is used gasses fuel such asliquified petroleum gas (LPG). The complete combustion are influence by three reason they are Air Fuel Ratio (AFR),homogeneity of mixture, and temperature of combustion. The complete combustion can be seen from content of exhaustemission. From the reason, researcher was did the research to know the influence of AFR toward the exhaust emission ofLPG fueled in the combustion chamber of Helle-Shaw Cell model.This experiment was did in the combustion chamber of Helle-Shaw Cell model with varieted the Air Fuel Ratio(AFR). The ratio is take from 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, and 21:1. The data that was observed are percentagesof carbon monoxide (CO), carbon dioxide (CO2), oxygen (O2) and hydrocarbon (HC).From result the research was get that the increasing of AFR from 14:1 to 20:1, the percentages of CO, O2, and HCare decrease but the percentages of CO2 is increase and in AFR 21:1 is occur decrease of CO2, while the percentage othergases are increase. To the LPG fuel stoichiometry of AFR is occur in 20:1. In stoichiometry of AFR the exhaust emission ofCO, O2, and HC are the most minimum but CO2 is the most maximum.
Keywords: LPG fueled, Air Fuel Ratio, exhaust emission